A Comparative Study of the Relationship Between Happiness and Reason in the Views of Socrates and Plato, with Emphasis on the Interpretation of Alexander of Aphrodisias and Abu Nasr al-Farabi - Al-Mesilini, Seyed Zuhair (Journal of Ecohumanism, 2024)
This article presents a comparative study of the relationship between happiness and reason from the perspectives of Socrates and Plato, with an emphasis on the interpretations of Alexander of Aphrodisias and Abu Nasr al-Farabi. The primary goal of this research is to analyze and compare the views of these two Greek philosophers regarding the concept of happiness and the role of reason in achieving it. Additionally, relying on the interpretations of Alexander and al-Farabi, we aim to explore the influence of these ideas on Islamic philosophy. The research methodology involves textual analysis and comparative examination of the primary works of Socrates and Plato, as well as the interpretations of Alexander of Aphrodisias and al-Farabi. The results of this study reveal that, while Socrates views happiness as a moral and rational goal, Plato emphasizes the role of reason in attaining happiness through the knowledge of truth and the good. This research holds particular significance for understanding the interaction between Greek and Islamic philosophy, demonstrating how later interpretations can affect the continuity and evolution of philosophical thought.